"Saluage soyl, far from Parnasso Mount": Spenser and Shakespeare in contemporary Irish writing. Issue 11 (31st July 2018) - Grogan, Jane
Abstract: This essay studies the literary politics of the reception of Spenser and Shakespeare in contemporary Irish writing, theatre, and public culture. Often conceived as a project of recovery or restitution, or as a niche interest for urban élites, the mixed fortunes and contrasting politics of Shakespeare and Spenser in 20th‐ and 21st‐century Ireland testify to the still sensitive politics of settlement and plantation, as well as the blind spots of nationalism and the national model of Irish literature. Focussing primarily on the current century, this essay traces crucial lines of reception back to W. B. Yeats and the Irish literary revival, pausing over Frank McGuinness's important play Mutabilitie (1997), which dared to imagine and provocatively recast both Shakespeare and Spenser's habitation in Ireland. That project found little support, just months before the Good Friday agreement was signed, but it stands over and guides a significant body of work in Irish drama and poetry in ways that have yet to be fully unpacked. Yet the contrast remains between the hero and the whipping boy, a congenial Shakespeare and a cruel Spenser, in literary engagements with Tudor Ireland. Although Shakespeare has generally been heralded as an enabling or emancipatory figure for Irish writers, this essay proposes that a richer and more radical politics can be accessed by the thornier route of confronting Spenser's place in Irish culture and history. The essay concludes by outlining a recent flourishing of interest in Spenser that seeks to exploit his potential for Irish culture and politics in these new, more honest but more challenging ways.